Nanostructured lipid carriers (NLCs): A comprehensive review of drug delivery advancements - Panwar, Pramesh; Kumar, Saurabh; Chand, Pallavi; Chauhan, Ashish Singh; Jakhmola, Vikash (Creative Pharma Assent, 2025)
Background: Nano-structured lipid carriers (NLCs) have emerged as a significant advancement in lipid-based drug delivery systems. Compared to Solid Lipid Nanoparticles (SLNs), NLCs offer improved drug loading capacity, stability, and controlled release profiles. Objective: This review article explores the structural and functional benefits of NLCs, their enhanced bioavailability, and their potential in targeted therapeutic agent delivery. Methodology: We investigated the unique combination of solid and liquid lipids in NLCs, which creates an internal structure for improved drug encapsulation and sustained release. Various methods were analyzed for their contribution to NLC efficacy, including high-pressure homogenization and solvent emulsification. Results and Discussion: NLCs demonstrated encapsulation efficiency ranging from 85–95%, with particle sizes between 100–300 nm. Drug release was sustained over 24 hours, affirming their effectiveness in controlled drug delivery. Applications of NLCs were highlighted across diverse delivery modes, including topical, pulmonary, oral, parenteral, and ocular. Challenges such as scaling production, overcoming biological barriers, and ensuring regulatory compliance were also addressed. Conclusion: NLCs present a promising future in pharmaceutical sciences, with the potential to improve therapeutic outcomes in complex diseases like cancer and neurodegenerative disorders. Continued research into NLC formulations is critical for advancing patient outcomes and addressing global health challenges.